Un caso inusual de eutrofización en el Embalse Río Tercero: el posible rol de dos bioinvasores - Mariñelarena, Alejandro Jorge (2016)
The trophic state is usually defined by the concentrations of total phosphorous and chlorophyll a. Besides the input of nutrients from catchment, the internal process can modify the trophic state in reservoirs and lakes. Embalse Río Tercero is a multipurpose reservoir that has been object of a limnological study since 1996, as a requirement of the Nuclear Power Plant that uses the water for cooling. Invasive species have been reported in this reservoir: the mussel Limnoperna fortunei Dunker 1857, since 1996 and the dinoflagellate Ceratium hirundinella (O.F.Müller) Dujardin 1841, since 1999. As a result of their successful colonization, some characteristics of water quality and plankton composition have been modified. Despite this, during a long time period, the trophic state has not been modified. However, since 2013 noticeable increases in phosphorous and clorophyll a have been detected, and C. hirundinella reached exceptional abundances and became the dominant algae. Coincidentally, L. fortunei almost disappeared without any apparent reason. We intended to interpret the long-term tendencies of main trophic variables, and hypothesized some explanations for the population changes of C. hirundinella.